COVID-19 Vaccines: Current Understanding on Immunogenicity, Safety, and Further Considerations - He, Qian; Mao, Qunying; Zhang, Jialu; Bian, Lianlian; Gao, Fan; Wang, Junzhi; Xu, Miao; Liang, Zhenglun (Frontiers in Immunology, 2021)
The world has entered the second wave of the COVID-19 pandemic, and it’s intensity is significantly higher than that of the first wave of early 2020. Many countries or regions have been forced to start the second round of lockdowns. To respond rapidly to this global pandemic, dozens of COVID-19 vaccine candidates have been developed and many are undergoing clinical testing. Evaluating and defining effective vaccine candidates for human use is crucial for prioritizing vaccination programs against COVID-19. In this review, we have summarized and analyzed the efficacy, immunogenicity and safety data from clinical reports on different COVID-19 vaccines. We discuss the various guidelines laid out for the development of vaccines and the importance of biological standards for comparing the performance of vaccines. Lastly, we highlight the key remaining challenges, possible strategies for addressing them and the expected improvements in the next generation of COVID-19 vaccines.